2006
DOI: 10.1002/jso.20546
|View full text |Cite
|
Sign up to set email alerts
|

High expressions of CD105 and VEGF in early oral cancer predict potential cervical metastasis

Abstract: Besides the image studies, the expressions of both CD105 and VEGF could be useful to guide the elective treatment for clinical N0 neck in early oral cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
44
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 34 publications
8
44
1
Order By: Relevance
“…The expression of CD105 observed by different researchers in OSCC was significantly higher i.e., to the extent of 75% of cases [25,[27][28]. Expression of CD 105, in OSCC patients habituated to tobacco, in this present study was observed in 13 of 20 cases (65%) [Table/ Fig-7].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The expression of CD105 observed by different researchers in OSCC was significantly higher i.e., to the extent of 75% of cases [25,[27][28]. Expression of CD 105, in OSCC patients habituated to tobacco, in this present study was observed in 13 of 20 cases (65%) [Table/ Fig-7].…”
Section: Discussionsupporting
confidence: 52%
“…Endoglin CD 105 expression in OSCC was also studied by these researchers and are considered to be significant [24,25,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…One of the first papers about the correlation between VEGF and angiogenesis was published by Artese et al in 2001, but no correlation was found between intensity of VEGF positivity and histological grading or lymph node status in OSCC [51]. Some studies depicted that VEGF-positive carcinoma had significantly poorer survival [52,53]. Other articles demonstrated a correlation between VEGF expression and survival.…”
Section: Vegf In Osccmentioning
confidence: 99%
“…Previous studies indicate that strong expression of CD105 in tumor-related, newly generated vascular endothelium is a more accurate index for judging endothelial reproductive state, and it is closely related to tumor generation and metastasis [24][25][26][27] . Contrasting with endothelial cell markers such as CD31, CD34 and Ⅷ factor-related antigens, the difference is that CD105 as a marker of angiogenesis is only strongly expressed in vascular endothelial cells of tumor tissues at the reproduction stage (i.e.…”
Section: Discussionmentioning
confidence: 99%